Pan-genome wide association study of Glaesserella parasuis highlights genes associated with virulence and biofilm formation - Zhou, You; Jiang, Dike; Yao, Xueping; Luo, Yan; Yang, Zexiao; Ren, Meishen; Zhang, Ge; Yu, Yuanyuan; Lu, Aiping; Wang, Yin (Frontiers in Microbiology, 2023)
G. parasuis is a gram-negative bacterium that causes fibrotic polyserositis and arthritis in pig, significantly affecting the pig industry. The pan-genome of G. parasuis is open. As the number of genes increases, the core and accessory genomes may show more pronounced differences. The genes associated with virulence and biofilm formation are also still unclear due to the diversity of G. parasuis. Therefore, we have applied a pan-genome-wide association study (Pan-GWAS) to 121 strains G. parasuis. Our analysis revealed that the core genome consists of 1133 genes associated with the cytoskeleton, virulence, and basic biological processes. The accessory genome is highly variable and is a major cause of genetic diversity in G. parasuis. Furthermore, two biologically important traits (virulence, biofilm formation) of G. parasuis were studied via pan-GWAS to search for genes associated with the traits. A total of 142 genes were associated with strong virulence traits. By affecting metabolic pathways and capturing the host nutrients, these genes are involved in signal pathways and virulence factors, which are beneficial for bacterial survival and biofilm formation. This research lays the foundation for further studies on virulence and biofilm formation and provides potential new drug and vaccine targets against G. parasuis.